A Study of Thermoelectric Performance of TlGaSe2 Layered Dichalcogenides from First‐Principles Calculations: Vacancy Defects Modeling and Engineering. Issue 1 (9th November 2021) - Çaydaşı, Murat; Mintaş, Mehmet Fatih; Chumakov, Yurii M.; Volz, Sebastian; Cengiz, Asuman; Seyidov, MirHasan Yu.
Abstract : Herein, the thermoelectric performance of TlGaSe 2 ternary layered dichalcogenides is evaluated by applying ab initio density functional theory calculations combined with Boltzmann's transport equation. A novel approach to design the intrinsic structural defects via Se‐anion vacancies in unit cell has been developed. Two kinds of Se ‐vacancy defects in host TlGaSe 2 crystal lattice are engineered: the single vacancy defect induced intrinsically in the unit cell ( 1 × 1 × 1 ) and in the supercell lattice ( 1 × 1 × 4 ). It is found that the electrical transport properties and thermoelectric efficiency of this semiconductor could be significantly altered by introducing Se‐vacancy states into crystalline structure. In addition, simulation shows that inclusion of Se‐vacancy defects significantly improves the thermoelectric efficiency as well as the thermoelectric power factor and figure of merit ( ZT ) values of this compound. Additionally, the thermoelectric performance of TlGaSe 2 is estimated by means of the electronic fitness function calculations in the valence and conduction edges. The results demonstrate that TlGaSe 2 with introduced Se ‐vacancies may be a perspective material for thermoelectric applications. Abstract : Herein, the effects of Se vacancies on the electronic thermal conductance, electrical conductance, Seebeck coefficient, figure of merit and electronic fitness function of TlGaSe2 layered semiconductor are theoretically studied. The findings indicate that Se‐vacancies can improve the thermoelectric performance of TlGaSe2 . This work provides concrete ways to enhance the thermoelectric performance of TlGaSe2 by defect engineering and modeling.